(untitled) (Medico Legal Update, 2021)
Forensic investigation of a gunshot related death can be a challenging process .When ascertaining the manner of death, the forensic expert should be careful, as, attempts are not uncommon to disguise homicides as suicides. Abnormal and unusual location of gunshot wound adds to this suspicion. The case under discussion highlights the role of a forensic expert in the ascertainment of the manner in firearm deaths. The deceased was a criminal who was absconding and when his where about were revealed to the investigating agency, he was followed to arrest but, upon reaching the spot in the sugarcane fields, there was exchange of fire and his dead body was found with the weapon lying near him. A thorough complete autopsy and detection of gun powder residue on hands lead to the unfolding of this mystery.